RUSSIA FOREIGN MINISTRY AND THE STATE DUMA DURING THE FIRST WORLD WAR - S. I. Chernyavskiy (Vestnik MGIMO-Universiteta)
The article studies the cooperation between the Russian Foreign Ministry and the State Duma during the First World War. A hundred years ago, the Russian parliament made the first real steps in democratization of public administration. MPs to the best of their ability and within the limits of the emperor’s powers sought to modernize the outdated system of monarchical rule. They were pushed by the tragic conditions of the First World War in which Russia was plunged by the royal family. The February Revolution of 1917 breathed new strength into the political struggle unfolding in Russia, it forced many conservative oriented public administrators to support the efforts of the MPs to establish a republican form of government. Russian diplomats also contributed to the effort when they assisted thousands of Russians who were caught up in captivity in hostile countries, as well as prisoners of war and seriously wounded. Using archival documents and memoirs, the author observes the evolution of the relationship between the Ministry of Foreign Affairs and the emerging civil society and how these changing relationships influenced the work of Russian diplomatic missions. This complex set of relationships evolved around issues faced by the authorities during the First World War and the February Revolution. Methodologically, the author relies on institutional approach and partially on the Annals school, analyzing the subject matter taking into account the specific historical conditions. In addition, the study uses elements of diachronic analysis, a comparison of the post-revolutionary and post-Soviet restructuring of diplomatic institutions in Russia, which demonstrates how deep the institutional memory can be under conditions of a consistent change in the socio-political structure.